Applicability of forced convection heat transfer topology optimization methods at the cell scale and heat exchanger core scale - Zhang, Zhaoda; Zhang, Xiaokai; Duan, Jiateng; Liu, Yu; Yan, Guanghan; Sun, Mingrui; Song, Yongchen (Applied thermal engineering, 2025)
•Effective parameters with porosity curves of the Weaire Phelan structure was built.•Topology optimization law of under different cases in turbulent flow is explored.•Provides a macro-topological initial design framework for large-scale structures.•Up to 80.6 % improvement in overall heat transfer performance of heat exchangers. Topology optimization methods can effectively guide the optimized layout of foam porous structures, but further research is needed on optimized structures under high-velocity conditions and at heat exchanger scales. This study provides a manufacturable, high-performance macro-topological initial design framework for large-scale structures. Relationships between different effective parameters and porosity are established, which serve as simulation parameters for porous medium models such as the non-Darcy model and the local thermal equilibrium model. Additionally, a comparison is made between the simulation results of the porous medium model and the real model, as well as experimental data. The topology optimization method employed is based on density model, with the inverse of the performance evaluation criterion as the optimization objective, subject to constraints on the overall porosity of the optimized region. The research findings indicate that the porous heat exchange device designed using topology optimization can reduce the pressure drop by up to 33.5 % compared to uniform structures, while enhancing the overall heat transfer performance (OHTP) by up to 53.4 %. This improvement primarily stems from optimized flow patterns that mitigate pressure drop and enhance heat transfer. Furthermore, a scaling study of the unit cell arrangement optimization results reveals that the optimized arrangement maintains a reduction in pressure drop of 37.6 % and an improvement in the OHTP of 80.6 % even under scaled-up conditions.